Key drivers of digital banking adoption in Malaysia: The role of convenience and user perceptions from Technology Acceptance Model perspectives (TAM) - Othman, Siti Nur Amira; Ku Abd Aziz, Ku Nur Ilyani; Aminaddin, Nabihah; Anuar, Muhammad Ashraf (Journal of Islamic, Social, Economics and Development, 2026)
The rapid advancement of information and communication technology has transformed the banking sector, leading to increased adoption of digital banking services. This study aims to examine key drivers of digital banking adoption in Malaysia: the role of convenience and user perceptions by focusing on three key factors: convenience, perceived ease of use, and perceived usefulness, grounded in the Technology Acceptance Model (TAM). A quantitative research approach was employed using primary data collected from 424 respondents in Malaysia. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to evaluate the proposed relationships. The findings reveal that all three factors convenience, perceived ease of use, and perceived usefulness have a significant positive influence on behavioural intention to adopt digital banking. Among these, perceived usefulness emerged as the strongest predictor, followed by convenience and perceived ease of use. The results indicate that users are more likely to adopt digital banking when they perceive it as beneficial, easy to use, and convenient for their daily financial activities. This study contributes to the existing literature by providing empirical evidence on digital banking adoption in the Malaysian context, particularly among young adults. The findings offer practical insights for financial institutions and policymakers to enhance digital banking strategies by improving system usability, functionality, and accessibility. Future research is recommended to include a broader demographic scope and additional variables to further strengthen the understanding of digital banking adoption behaviour.